Power quality enhancement using fully informed particle swarm optimization based DSTATCOM in distribution systems - Shankar, Moguthala; Kumar, R. Senthil (International Journal of Applied Power Engineering (IJAPE), 2024)
To compensate for the reactive power, inverter-based conditioners have been utilized in recent years due to their faster response. Distribution static synchronous compensator (DSTATCOM) has been utilized to enhance power quality in power system that is an inverter-based device that is widely utilized. To control this type of equipment, a proportional integrated (PI) controller has been utilized to control most of the equipment with respect to certain parameters. The performance of the controller basically does not meet the expectations because of the dynamics and nonlinearity of a system parameters. In this present paper, a probabilistic neural network has been used in a controller with a fully informed particle swarm optimization (FIPSO) algorithm to generate a suitable weight for controlling the axes of various parameters of DSTATCOMs. Using MATLAB/Simulink software, simulations were performed, and the responses were monitored with particular regard to the reference reactive parameter. The results are compared. DSTATCOM improves power system damping.